Terrorism or Insurgency in the Sahel? (Comillas Journal of International Relations, 2023)
Since the French military intervention in Mali ten years ago, the security situation in Sahel has only worsened. The expansion of armed groups linked to Al-Qaeda and the Islamic State is posing a serious threat to the stability of a region on Europe's doorstep. The policies that the European Union and Sahel countries have adopted against these threats seem to have been reduced to counter-terrorism, without much success by all accounts. But are we dealing with terrorist groups, or might they not be better defined as insurgent elements? If so, it could be argued that the European initiatives have stemmed from an unfocused interpretation of reality, which would necessarily result in a failure in the achievement of their objectives. This article will analyze these policies, the reality of these armed groups, and point out the differences between counterinsurgency and counterterrorism, trying to help the reader understand the reasons for the current situation.
Keywords: Terrorism; insurgency; Sahel; Azawad; Mali; JNIM; ISGS; Barkhane